2008
DOI: 10.1007/s12306-007-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Free fibula flap for humerus segmental reconstruction: report on 13 cases

Abstract: In the period between 1994 and 2004, 13 patients (10 male, 3 female) presenting with post-traumatic defects to the humerus were treated with vascularised fibula graft. Age ranged from 21 to 62 (mean 37) years. Length of the bony defect ranged from 6 to 16 cm. Graft fixation was performed with plates in 12 cases, and in one case only screws were used. All patients were clinically reviewed between 120 days and 14 months after surgery. In one patient the flap was lost and a second free fibula flap was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The newly emerging membrane induction technology requires a second surgical treatment, which greatly increases the patient's pain and medical expenses [ 19 ]. The microsurgery technique will increase the damage to the donor site, making it unacceptable for some patients [ 20 ]. Once improperly handled, the infection recurs, which will lead to failure of implant fixation or bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The newly emerging membrane induction technology requires a second surgical treatment, which greatly increases the patient's pain and medical expenses [ 19 ]. The microsurgery technique will increase the damage to the donor site, making it unacceptable for some patients [ 20 ]. Once improperly handled, the infection recurs, which will lead to failure of implant fixation or bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The two patients with the most limited recovery were reconstructions involving resection of the humeral head, which reflects findings of other authors who have also reported limited functionality following reconstruction of the glenohumeral joint. 14,28 While both patients with humeral head reconstructions in our own series reported excellent adaptive functionality, one patient was considering an arthroplasty for persistent pain at most recent follow-up 3 years postoperatively. The lower MSTS scores for these two patients also help explain the lower average MSTS score for upper extremity compared with lower extremity reconstructions.…”
Section: Discussionmentioning
confidence: 83%
“…12,13 Surgeons have utilized the free fibula transfer to reconstruct a myriad of humeral defects when nonvascularized bone graft or prosthesis would not be sufficient. [14][15][16] However, there conceivably exist circumstances where a free fibula flap is not an option, as in our shoulder arthrodesis case. Patients with multiple previous surgeries and attempts at wound coverage may have significant disruption of the regional vasculature.…”
Section: Discussionmentioning
confidence: 85%